2020
DOI: 10.1002/zoo.21531
|View full text |Cite
|
Sign up to set email alerts
|

Gum feeder as environmental enrichment for zoo marmosets and tamarins

Abstract: Tamarins and marmosets are small‐bodied social callitrichines. Wild callitrichines feed on exudates, such as sap and gum; particularly, marmosets are mainly gummivores, while tamarins consume gums only occasionally and opportunistically. Zoo marmosets and tamarins are usually provided with gum arabic as an alternative to the exudates normally found in the wild. The aim of this study was to evaluate the effects of a gum feeder on the behavior and well‐being of four zoo‐managed callitrichines. We studied four co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Callimico are not obligate gum feeders, although it forms part of their opportunistic diet in the wild [5] and is important to the behavioral and physical needs of captive callitrichids [42]. This study did not examine daily nutritional provision, but gum was only reported as a component of enrichment by 69% of zoos, although it can be an easy and effective method of promoting positive welfare [57]. One collection reported that fecal consistency improved following the introduction of gum enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Callimico are not obligate gum feeders, although it forms part of their opportunistic diet in the wild [5] and is important to the behavioral and physical needs of captive callitrichids [42]. This study did not examine daily nutritional provision, but gum was only reported as a component of enrichment by 69% of zoos, although it can be an easy and effective method of promoting positive welfare [57]. One collection reported that fecal consistency improved following the introduction of gum enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies with various species of zoo animals such as lions [21], marmosets [22], chimpanzees [23], orangutan [24], lemurs [25], and African wild dogs [26] have demonstrated the positive impact of environmental enrichment on well-being outcome including physiological responses to stress and boredom.…”
Section: Discussionmentioning
confidence: 99%
“…Aggression can have direct, immediate impacts in the form of physical injury, which is typically assumed to induce pain and is generally interpreted as negative welfare (reviewed by Martins et al, 2012). A feeding regime that employs demand on the part of the animal, as is often done for terrestrial zoo animals (Regaiolli et al, 2020), has been done for farmed fishes but has not been done with zoo and aquarium fishes as far as we know (Almazán‐Rueda et al, 2004; Noble et al, 2007). Quantitative behavioral observations would be an excellent way for zoos and aquariums to enhance their feeding regimes for individual bony fishes.…”
Section: Discussionmentioning
confidence: 99%